An Investigation of Pain Related Disability with Movement Quantity and Quality in Pre-Professional Dancers - Hendry, Danica (Curtin University, 2021)
This thesis explored the relationship between dancers' movement quantity and quality with pain outcomes. Machine learning models applied to wearable sensor data that were capable of field-based, objective quantification of dancers' movement quantity and quality were developed. This system was used in a longitudinal, field-based study to explore the relationship of pre-professional, female dancers movement quantity and quality with pain and pain related disability.